Living on the edge: A continental‐scale assessment of forest vulnerability to drought. (20th May 2021) - Peters, Jennifer M. R.; López, Rosana; Nolf, Markus; Hutley, Lindsay B.; Wardlaw, Tim; Cernusak, Lucas A.; Choat, Brendan
Abstract: Globally, forests are facing an increasing risk of mass tree mortality events associated with extreme droughts and higher temperatures. Hydraulic dysfunction is considered a key mechanism of drought‐triggered dieback. By leveraging the climate breadth of the Australian landscape and a national network of research sites (Terrestrial Ecosystem Research Network), we conducted a continental‐scale study of physiological and hydraulic traits of 33 native tree species from contrasting environments to disentangle the complexities of plant response to drought across communities. We found strong relationships between key plant hydraulic traits and site aridity. Leaf turgor loss point and xylem embolism resistance were correlated with minimum water potential experienced by each species. Across the data set, there was a strong coordination between hydraulic traits, including those linked to hydraulic safety, stomatal regulation and the cost of carbon investment into woody tissue. These results illustrate that aridity has acted as a strong selective pressure, shaping hydraulic traits of tree species across the Australian landscape. Hydraulic safety margins were constrained across sites, with species from wetter sites tending to have smaller safety margin compared with species at drier sites, suggesting trees are operating close to their hydraulic thresholds and forest biomes across the spectrum may be susceptible to shifts in climate that result in the intensification of drought. Abstract : Forests face an increasing risk of extreme droughts and high temperatures under a changing climate. To understand the vulnerability of Australia's native forests to drought‐induced hydraulic dysfunction, we conducted a continental‐scale study of physiological and hydraulic traits from tree species growing in contrasting environments. We found (1) aridity strongly influences plant hydraulic traits; (2) hydraulic vulnerability (P50 ) tightly couples with the plant water stress experienced by each species (Ψmin ); and (3) hydraulic safety margins provide little protection, particularly for wet habitat species, suggesting many forest biomes may be susceptible to climate shifts.